Legal Protection for Auction Buyers Who Are Disadvantaged Regarding the Validity of the Auction Deed Attended by Online Auction Officials (E-Auction) - Safa Luthfia Gumilang; Not. Ranti Fauza Mayana; Amelia Cahyadini (IHSA Institute, 2024)
This research aims to investigate legal protection for auction buyers who experience losses related to the validity of the relaas deed attended by online auction officials (e-auction). This research uses a normative legal approach Legislative Approach (Statute Approach) and Conceptual Approach (Conceptual Approach). This legislative approach is carried out by reviewing the laws and regulations that regulate the Auction implementation regulations. The research results show that legal certainty regarding the validity of the auction deed attended by online auction officials (e-auction) is very important to ensure that the auction meets the established principles, such as openness, competition, fairness, legal certainty and accountability. This is in line with the mandate of PMK 213/2020. The auction minutes prepared by the auction official are authentic deeds that reflect the implementation of the auction. Legal protection for auction buyers who suffer losses related to the validity of the relaas deed attended by online auction officials includes provisions in the Civil Code, PMK 213/2020, as well as other related regulations. Auction officials, both in Class I and Class II, have the authority stipulated by law to carry out auctions and prepare Auction Minutes as proof of the validity of the auction.